On certain differential game for Lanchester's equations - Liapunov, A. (Lithuanian Mathematical Journal, 1970)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:А. Н. Ляпунов. Об одной дифференциальной игре для уравнений типа ЛанчестераA. Liapunovas. Apie vieną diferencialinį lošimą Lančesterio tipo lygtims